Energy homeostasis model for electrical and thermal systems integration in residential buildings: a means to sustain distributed generation systems integration - Yanine, Fernando; Sahoo, Sarat Kumar; Sanchez-Squella, Antonio; Barrueto, Aldo; Krishna Rao, Challa (Frontiers in Energy Efficiency, 2023)
Integrating renewables in the distribution sector is a rapidly growing reality in many countries, amongst which Chile's stands out with an increasingly diversifiable electricity matrix. However, incorporating RES into the electricity distribution sector is altogether a steep climb at present, and seen by some as a formidable challenge for utilities. Likewise, the introduction of the Smart Grid agenda in Chile is imposing new challenges to electric utilities, mainly from a regulatory and technical viewpoint. In spite of this, big players like ENEL are moving forward decisively to meet this challenge, together with academia experts. We present a model comprising a community we term a sustainable block™ representing an average residential building in Santiago, Chile, which aims to take advantage of Law 20,571 in Chile that allows independent electric power generators to benefit by selling electricity to the grid and also allows independent consumers (mostly residential) to generate part or all of their energy needs while connected to the grid. The community may consume electricity from the microgrid with energy storage, operated by the local electric company, supplying electricity to the 60-apartment complex of various sizes. The model comprises a set of energy homeostasis management strategies that have been designed in the power control and energy management system to balance supply and demand while optimizing the use of green energy. The energy homeostasis model optimizes the microgrid supply while injecting excess power to the grid. In this context, the community residents exhibit different consumption profiles and may willingly participate of the sustainable energy strategy as prosumers, displaying a thriftier consumption, and enjoying a lower electric bill while using more renewables. Energy homeostasis of electric power systems seeks to maintain a dynamic balance between supply and demand and is being currently discussed with ENEL Chile as part of the intelligent control options for the introduction of distributed generation systems tied to the grid, in order to complement their electric power distribution services. The role of energy storage as well as the role of prosumers are the key enabling factors of energy homeostasis and their interaction are highlighted in the overall analysis.